Modeling of the Thermo-Deformation Behavior in a Laser-Hardened “Plunger – Barrel” Pair Considering Wear Effects - Huseynov, A.G.; Asadov, Sh.N.; Huseynli, F.S.; Asadov, Sh.A. (Herald of Azerbaijan Engineering Academy, 2025)
In this study, the elastic state arising at the interface between a laser-hardened plunger and its mating barrel was investigated. Laser surface hardening significantly enhances the material hardness and tribological performance, which leads to a more favorable distribution of temperature and deformation in the contact zone. In the analysis, the plunger surface was modeled as a periodic structure and examined within the framework of elasticity theory using the Kolosov–Muskhelishvili complex potentials method. The boundary conditions were simplified through Fourier series expansion, allowing the distribution of normal and frictional stresses within the contact area to be determined analytically. This approach enables a more accurate assessment of the influence of surface hardening on contact temperature and carries practical significance for improving the operational performance, reliability, and wear resistance of plunger-type components. The results of the research align with current scientific directions pursued at the “Department of Special Technologies and Equipment” of the Azerbaijan Technical University, and provide a solid theoretical foundation for industrial applications in the fields of tribology and contact mechanics.